Potensi Vegetasi Semak di Kelurahan Bangkal, Palam dan Sungai Tiung, Kecamatan Cempaka, Banjarbaru - Dienny Redha Rahmani; Gunawan Gunawan (Bioscientiae, 2021)
A good urban structure and activity need a green spaces to increase its ecological function. However, trees will not fully be able to fill an important space in urban areas while the shrub woody vegetation has the potential to fill that space. Therefore, the aim of this study is to determine theÂ  potential of shrub as a constituent of urban vegetation so it can be used as material information about the planning of land use in the district of Cempaka. This sudy was conducted by determining the three sampling stations and 3 plots of 4m x 4m in wide on each station with data based on a map of shrub green space in District of Cempaka using purposive sampling method, the analysis performed includes the analysis of shrub canopy, measured environmental parameters, and data were analyzed with analysis of canopy volume, Pearson correlation analysis and analysis of Importance Value Index (IVI). Shrub vegetation estimation results indicate that the shrub canopy volume in the district of Cempaka is up to 22,462,878.50 m3 in the bush land area of 5675.116 hectares. Pearson correlation analysis showed that the shrub canopy volume in the district Cempaka effect on changes in environmental factors. Besides the most dominant species is Ficus fistulosa Reinw. ex Bl with IVI of 56.1%. Based on the results obtained can be concluded that the shrub has potential as a constituent of vegetation in urban green space.